2015
DOI: 10.1111/jopr.12424
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of Alumina, Zirconia, and Lithium Disilicate Surface Roughness Caused by Two Scaling Instruments

Abstract: Comparison of profilometer readings before and after instrumentation, carried out with different hand scaling instruments, highlighted both a statistically and clinically relevant increase in material roughness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
(49 reference statements)
3
18
1
Order By: Relevance
“…However, the surfaces of the lithium disilicate and zirconia discs were significantly roughened after repeated scaling. A previous study revealed that the use of a titanium-based or stainless steel periodontal curette increased the surface roughness of lithium disilicate and zirconia 27. The result was in consistent with the findings of the current study, showing that the ultrasonic scaling has a negative effect on the surface morphology of ceramic material.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the surfaces of the lithium disilicate and zirconia discs were significantly roughened after repeated scaling. A previous study revealed that the use of a titanium-based or stainless steel periodontal curette increased the surface roughness of lithium disilicate and zirconia 27. The result was in consistent with the findings of the current study, showing that the ultrasonic scaling has a negative effect on the surface morphology of ceramic material.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, there were studies on the effects of scaling on restorative materials or on the changes in surface roughness in relation to scaling methods, few studies have been reported about the surface changes by repeated ultrasonic scaling and subsequent intraoral polishing. 26 27 Therefore, the aim of this study was to evaluate the surface roughness changes in three different restorative materials (nickel-chromium alloy, lithium disilicate glass ceramic, and zirconia) after repeated treatment with an ultrasonic scaler and subsequent polishing with intraoral polishing systems. The null hypothesis was that there would be no difference in surface roughness of restorative materials according to the materials and in each of the three treatment steps (before scaling, after repeated scaling, and surface polishing).…”
Section: Introductionmentioning
confidence: 99%
“…Tamura et al [38] reported that the Vickers hardness of titanium nitride was 1300. This was in contradiction to Vigolo et al [39] who recorded equal increase in the median surface roughness profile value for both steel curette and titanium curette.…”
Section: Discussioncontrasting
confidence: 96%
“…After screening, 26 studies were selected for a full-text evaluation to assess their eligibility according to the selection criteria. After the evaluation, 11 studies [ 25 26 27 28 29 30 31 32 33 34 35 ] were included for the final review. Fifteen studies did not meet the inclusion criteria and were excluded for the following reasons: the study did not investigate interventions for decontamination purposes (n=9); the study did not use zirconia as an implant material (n=5); or there was no comparator or control group (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…After an evaluation of the selected studies, only 1 study was found to assess zirconia implants [ 25 ] as a test sample, whereas 10 studies [ 26 27 28 29 30 31 32 33 34 35 ] used zirconia discs to represent an implant surface. In most studies, the implant surface roughness was measured with mean roughness (R a ) or mean height (S a ) as the surface outcome parameter.…”
Section: Resultsmentioning
confidence: 99%